STEADY FLOW SIMULATION IN OPEN CHANNEL USING STAGGERED GRID METHOD - Nurfathhiyah Hadiarti, Revi
The Saint-Venant equations describe dynamical aspects of open channel flow. The type of flows could be subcritical flow, supercritical flow or combination of those two types. In certain situation, the flow will be at steady state. To reach the steady state, we need appropriate boundaries according to its flow type. Simulations in this thesis used staggered grid method. In general, varying cross-section shapes and flow types were studied here. The cross-section shapes were prismatic and non prismatic then the topography were incline and a bump. Simulation result show a good agreement to the analytical solution and the reference.